ANALISIS RISIKO PENCAHAYAAN, VENTILASI DAN KEPADATAN PENGHUNI TERHADAP KEJADIAN TB PARU DESA TANGGUL KULON KECAMATAN TANGGUL KABUPATEN JEMBER - Prasetyowati, Irma (IKESMA, 2009)
Tuberculosis (TB) still becomes a urgent health problem in the world. According to WHO report, the one-third population is infected by Mycobacterium tuberculosa (M.tb), and there were more or less two million people per year who died caused by this disease. The spreading of the disease in Tanggul is still high. The objective of this research was to analysis the risk of lighting, ventilation and overcrowding of the house that causing the TB cases. This research was an observational analytic research using case control study design. The number of samples of this research was 64 respondents which consisted of 16 cases and 48 controls. The cases were the people who had positive TB Acid-Fast Bacill(AFB). The controls were the people who were not affected by TB. The Odds ratio analyses were used to find the risk of variable by calculating confident interval. The analysis showed that the less lighting were 4.2 times (95%Cl 1.181-14.937), less ventilation were 5.571 times (95%CI 1.403-22.120) and over crowding were 3.987 times (95%CI 1.006-15.802) more likely to have TB cases. It was suggested to lead people to always open the windows and doors every morning, and to use roofs from glass. Keywords: TB, lighting, ventilation, overcrowding